2021
DOI: 10.3390/cells10061321
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant B Cell Receptor Signaling in Naïve B Cells from Patients with Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic and ultimately fatal disease in which an impaired healing response to recurrent micro-injuries is thought to lead to fibrosis. Recent findings hint at a role for B cells and autoimmunity in IPF pathogenesis. We previously reported that circulating B cells from a fraction of patients, compared with healthy controls, express increased levels of the signaling molecule Bruton’s tyrosine kinase (BTK). However, it remains unclear whether B cell receptor (BCR) signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…According to the literature, B cells are closely related to the pathogenesis of IPF, especially the naive CD38dim B-cell population, which increases Bruton's tyrosine kinase (BTK) levels and promotes substrate level phosphorylation, which provides the basis for B-cell proliferation and promotes the development of IPF. CD25 expression on CD4 Tregs is a subpopulation of CD25 in the CD4 of natural regulatory T cells distributed in normal human and mouse peripheral blood and splenic tissues, which can inhibit T-cell proliferation and induce autoimmune diseases through antigenic nonspeci c mechanisms [13]. CD4 and CD25 proteins can increase the expression of the transcription factor Foxp3 [14].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, B cells are closely related to the pathogenesis of IPF, especially the naive CD38dim B-cell population, which increases Bruton's tyrosine kinase (BTK) levels and promotes substrate level phosphorylation, which provides the basis for B-cell proliferation and promotes the development of IPF. CD25 expression on CD4 Tregs is a subpopulation of CD25 in the CD4 of natural regulatory T cells distributed in normal human and mouse peripheral blood and splenic tissues, which can inhibit T-cell proliferation and induce autoimmune diseases through antigenic nonspeci c mechanisms [13]. CD4 and CD25 proteins can increase the expression of the transcription factor Foxp3 [14].…”
Section: Discussionmentioning
confidence: 99%
“…In DCM, the cardiac fibrosis, an important pathological characteristic, could be activated by multiple humoral and cellular factors, leading to the increased cardiac rigidity, decreased myocardial performance, and enhanced sudden death risk. Accumulated studies had revealed various immune cells (e.g., macrophages, CD8(+) T cells, and activated B cells) were involved in the development of cardiac fibrosis via directly activating cardiac fibroblasts or/and indirectly releasing pro-fibrotic cytokine 13 , 25 . COL3A1 , also named collagen type III alpha 1 chain, plays a significant role in encoding fibrillar collagen, contributing to the progression of fibrosis in extensible connective tissues such as lung, skin and the vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…In DCM, the cardiac brosis, an important pathological characteristic, could be activated by multiple humoral and cellular factors, leading to the increased cardiac rigidity, decreased myocardial performance, and enhanced sudden death risk. Accumulated studies had revealed various immune cells (e.g., macrophages, CD8(+) T cells, and activated B cells) were involved in the development of cardiac brosis via directly activating cardiac broblasts or/and indirectly releasing pro-brotic cytokine [13,25] . COL3A1, also named collagen type III alpha 1 chain, plays a signi cant role in encoding brillar collagen, contributing to the progression of brosis in extensible connective tissues such as lung, skin and the vascular system.…”
Section: Discussionmentioning
confidence: 99%